REAKTUALISASI PERMAINAN BAKIAK DALAM BINGKAI QUANTUM-VIRTUAL LEARNING: UPAYA MEMPERERAT INTERAKSI SOSIAL SISWA DI ERA DIGITAL - Siti Nur Tsumniyati; Ryan Dwi Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the decline in group cohesion and the rise of student egocentrism driven by the dominance of passive digital learning. To bridge this gap, this research integrates virtual learning technology with local wisdom through the traditional game Bakiak. Utilizing Classroom Action Research (CAR) with a descriptive qualitative approach, the instructional intervention applied the TANDUR cycle of the Quantum Learning model. Within this framework, a virtual simulator served as a cognitive and psychological conditioning medium before students engaged in direct social implementation on the field. The subjects were fourth-grade students at SDN Pedurungan Kidul 02, Semarang. Data were gathered through participant observation and in-depth interviews, then analyzed using the Miles and Huberman interactive model. The findings revealed a significant increase in interpersonal intelligence and a reduction in student social fragmentation. Although individualistic conflicts dominated student interactions during the initial cycle, this resistance was successfully mitigated by Cycle II. Students demonstrated enhanced social maturity, characterized by strengthened empathy and adaptive cooperative skills within groups. This study concludes that the convergence of digital innovation and local tradition can effectively synergize to restore student social dynamics. The practical implication underscores the urgency of reconstructing technology-based learning to remain oriented toward fostering humanistic character and student collectivity in the digital era.